2013
DOI: 10.1007/s10803-013-1862-3
|View full text |Cite
|
Sign up to set email alerts
|

The Autism Impact Measure (AIM): Initial Development of a New Tool for Treatment Outcome Measurement

Abstract: The current study describes the development and psychometric properties of a new measure targeting sensitivity to change of core autism spectrum disorder (ASD) symptoms, the Autism Impact Measure (AIM). The AIM uses a 2-week recall period with items rated on two corresponding 5-point scales (frequency and impact). Psychometric properties were examined using a large sample (n = 440) of children with ASD enrolled in the Autism Treatment Network. The exploratory factor analysis indicated four factors and resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 38 publications
0
78
1
3
Order By: Relevance
“…Sleep studies at 10 and 15 months post-Hi-Cy showed improvement in central apnea (0.6/hour and 0.8/hour, respectively) and hypopnea (9.4/ hour and 8.9/hour, respectively), with saturation nadir still at 86%. The markedly improved behavior and social interactions, as reported by parents and observed during assessment appointments by clinicians, were reflected by a modified AIM 16 score increase from 41 to 60.…”
Section: Figurementioning
confidence: 81%
See 1 more Smart Citation
“…Sleep studies at 10 and 15 months post-Hi-Cy showed improvement in central apnea (0.6/hour and 0.8/hour, respectively) and hypopnea (9.4/ hour and 8.9/hour, respectively), with saturation nadir still at 86%. The markedly improved behavior and social interactions, as reported by parents and observed during assessment appointments by clinicians, were reflected by a modified AIM 16 score increase from 41 to 60.…”
Section: Figurementioning
confidence: 81%
“…At 18 months post-Hi-Cy, parents reported markedly diminished hyperphagia, resolution of aggressive food-seeking behavior, normalization of pain perception, and markedly improved empathy with appropriate emotional responses. Accordingly, her modified autism impact measure ([AIM] range, 18-90) 16 score improved from 49 to 85. BMI declined to 30 (Z-Score +2.9), and a sleep study demonstrated average oxygen saturation of 95%, nadir of 91%, and no episodes of end tidal carbon dioxide >50 mm Hg.…”
Section: Casementioning
confidence: 99%
“…The network maintains a registry of children with ASD diagnosed in any of the participating centers. The details of the AS-ATN registry methodology have been previously published and data from this registry have been used by other researchers in the past (Coury et al 2009; Kanne et al 2014; Kuhlthau et al 2010; Lajonchere et al 2012; Perrin et al. 2012; Sikora et al 2012).…”
Section: Methodsmentioning
confidence: 99%
“…For example, in a previous study [19] children were not compliant with an oral motor assessment (Com DEALL Oro Motor Assessment [66]) possibly because of sensory sensitivities around the mouth. The last decade and a half of research on early intervention in autism has spurred the development of new measures sensitive to change from which the current trial benefits, such as the BOSCC [47] and the AIM [62]. Furthermore, we use a wide range of assessments to comprehensively ascertain the impact of the Point OutWords intervention, including measures of restricted and repetitive behaviour (BOSCC, SRS, AIM); some studies have found that improvement in communication skills can have a knock-on effect on the reduction of restricted/repetitive behaviours [9,67].…”
Section: Discussionmentioning
confidence: 99%
“…The AIM [62] is a 25-item parent-report questionnaire that measures changes in core autism symptoms, and which has strong test-retest and cross-informant reliability [62]. Mean differences in scores collected at baseline and post-intervention will be compared between the intervention and control groups.…”
Section: Autism Impact Measure (Aim)mentioning
confidence: 99%